Nanosized porous artificial enzyme as a pH-sensitive doxorubicin delivery system for joint enzymatic and chemotherapy towards tumor treatment. (13th July 2022) - Xu, Zhilu; Wang, Ting; Li, Jing; Zhang, Fang; Lou, Han; Zhang, Jian; Zhang, Wenhua; Zhang, Weifen; Zhou, Baolong
Abstract : A porous spherical artificial nanozyme (HF-900) prepared via pyrolysis of a porous organic polymer was used as drug carrier for efficient loading and highly selective pH-responsive delivery of doxorubicin (DOX) for the tumor joint nanotherapy. Abstract : Nanozymes are new emerging functional nanomaterials with intrinsic enzyme-like activity which could function as a highly-stable and low-cost alternative to natural enzymes. Here, a facilely and easily scalable spherical artificial porous nanozyme (HF-900) was prepared via direct pyrolysis of a porous organic polymer (POP) composed of cyclotriphosphazene and iron-porphyrin. HF-900 could function as an ideal drug carrier for efficient loading and highly selective pH-responsive delivery of doxorubicin (DOX), avoiding the premature release of a drug under normal physiological conditions, effectively. As a result, HF-900 could be used as a multifunctional nanoplatform combining the enzymatic and chemotherapy, significantly inhibiting the growth of solid tumor in vivo with negligible systemic toxicity. Our findings open up a new avenue for the rational design and preparation of artificial nanoenzyme in tumor treatment.